2011
DOI: 10.1186/1479-5876-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Shipping blood to a central laboratory in multicenter clinical trials: effect of ambient temperature on specimen temperature, and effects of temperature on mononuclear cell yield, viability and immunologic function

Abstract: BackgroundClinical trials of immunologic therapies provide opportunities to study the cellular and molecular effects of those therapies and may permit identification of biomarkers of response. When the trials are performed at multiple centers, transport and storage of clinical specimens become important variables that may affect lymphocyte viability and function in blood and tissue specimens. The effect of temperature during storage and shipment of peripheral blood on subsequent processing, recovery, and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 46 publications
3
56
0
Order By: Relevance
“…Studies conducted by Ahmann et al (2008) showed that tissue sample shipment on dry ice within USA did not have a drastic impact on plasma cell isolation, viability and RNA integrity. Olson et al (2011) had investigated the effects of overnight ambient temperature shipment at different seasons and samples subjected to 40°C for more than 8 h showed reduced viability. In Olson et al study, PBMCs were isolated for analysis and 4 color flow staining panel was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Ahmann et al (2008) showed that tissue sample shipment on dry ice within USA did not have a drastic impact on plasma cell isolation, viability and RNA integrity. Olson et al (2011) had investigated the effects of overnight ambient temperature shipment at different seasons and samples subjected to 40°C for more than 8 h showed reduced viability. In Olson et al study, PBMCs were isolated for analysis and 4 color flow staining panel was employed.…”
Section: Discussionmentioning
confidence: 99%
“…8 Samples (peripheral blood, bone marrow) were collected in lavender-top (K 2 EDTA,) or red-top (no additive) BD vacutainer tubes (Becton Dickinson). Lavender-top tubes were delivered to the laboratory within 2 hours of draw or shipped overnight at room temperature in insulated containers essentially as described 9 prior to processing. Samples were processed within 30 minutes of receipt according to established laboratory standard operating procedures.…”
Section: Research Sample Draws and Processingmentioning
confidence: 99%
“…DBS should be transported to the laboratory at ambient temperature within 24 h of collection (19,32 ). Blood, urine, saliva, DNA, or RNA shipped by commercial carrier may encounter extreme seasonal temperatures, and this factor should thus be accounted for in long-term large-scale multinational studies (51,98,99 ). Samples that must be shipped to a processing laboratory cannot be used for the most unstable biomarkers, or processing should begin in the field to ensure stability during transportation (7 ).…”
Section: Transport Of Biospecimensmentioning
confidence: 99%